Uma proposta para o despacho otimizado em geradores síncronos utilizando o algoritmo genético - Ragnev, Walter (2020)
In the electric energy market, load demands require the simultaneous generation of active and reactive energy by synchronous generators with their optimized dispatch, with lower losses and lower costs. For this optimization, the FPO - Optimal Power Flow is used, which establishes the most economical operation of the electrical system with the reduction of its losses to meet the loads, respecting the operational limits of the equipment and its operational reliability conditions, indicating the dispatch generation of each plant in the system. The presente work proposes a methodology for the dispacth of active and reactive power generation in synchronous generator sets using genetic algorithms based in electrical parameters and consumption characteristics of each machine in each synchronous generator set (turbine, generator and power transformer) in the plant. The proposed work shows practical examples of using these algorithms for use hydroelectric and thermoelectric power plants. In order to validate the proposed algorithm, the case studies were carried out in the southeast region of the State of São Paulo, where some cases of generation dispactch in hydroelectric and thermoelectric power plants were simulated and analyzed. The results obtained provide the operators of the plant an operating point for the synchronous generators with lower losses and lower operating costs, satisfying the generation requirements of the Nacional Electric System.